Information technologies in the construction of the field of radiation pollution of the locality and forecasting - Nagornyi, Yevhen I. (Kyiv National University of Construction and Architecture, 2024)
The article examines the improvement of information technologies in the construction of the field of radiation contamination of the area based on the measured values of the impact factors of a nuclear explosion. Forecasting uses summaries of radioactive contamination centers and meteorological information. This process is quite well formalized and its practical implementation does not present great difficulties in automated systems for monitoring the radiation environment.Studies have shown that with a large heterogeneity of the source data by location (the presence of significant zones in which measurements were not carried out), this approach can unjustifiably overestimate or underestimate the calculated values in these zones. The local interpolation method was used to correct this effect. It is based on the assumption of the presence of local linear dependencies in the source data.In automated radiation monitoring systems, interpolation methods are used in the presence of a widespread network of stationary sensors connected to communication channels.The interpretation of radiation reconnaissance data using interpolation methods does not allow using a priori information about the parameters of the cell and the conditions for the formation of radiation contamination of the area. Joint accounting in the processing of these data allows you to combine the stages of forecasting and detection of the actual situation into a single process.